Risk factors associated with severe adverse events in patients with relapsing polychondritis undergoing flexible bronchoscopy - Shao-Ting Wang; Jinglan Wang; Xiaoxing Gao; Keqi Chen; Kai-Feng Xu; Xinlun Tian (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Patients with relapsing polychondritis (RP) sometimes experience upper airway collapse or lower airway stenosis, and bronchoscopy may provide a valuable typical image to confirm the diagnosis. This study aimed to identify potential risk factors associated with severe adverse effects during bronchoscopy. Methods We performed a retrospective cohort study of 82 consecutive patients with RP hospitalized at Peking Union Medical College Hospital between January 1, 2012 and December 31, 2022. Clinical features and disease patterns were compared among patients with RP undergoing bronchoscopy with or without severe adverse effects. Binary logistic regression analysis was performed to identify the associated risk factors. Results For patients with RP undergoing bronchoscopy with severe adverse effects, the forced vital capacity (FVC), forced vital capacity percent predicted values (FVC%), and peak expiratory flow were significantly lower (P = 0.001, P = 0.001, and P = 0.021, respectively) than those in the non-severe adverse effect subgroup. Binary logistic regression analysis revealed that low FVC% (odds ratio, 0.930; 95% confidence interval, 0.880–0.982; P = 0.009) was an independent risk factor for severe adverse events in patients undergoing bronchoscopy. Conclusions Low FVC or FVC% suggests a high risk of severe adverse effects in patients with RP undergoing bronchoscopy. Patients with such risk factors should be carefully evaluated before bronchoscopy and adequately prepared for emergency tracheal intubation or tracheostomy.